Sites of the Early (Archaic) Stage of the Lyalovo Culture on the Upper Don - Roman V. Smol’yaninov; Alexey A. Kulichkov; Elizaveta S. Yurkina (Археология евразийских степей)
The authors put forward the thesis that ceramic materials with combed-denticulated-dotted ornamentation, which previously traditionally belonged to the Late Neolithic Rybnoozersk culture on the Upper Don, are completely similar to pottery assemblages of the Lyalovo culture early (archaic) stage in the Upper Volga region. At the same time, there is a similar time interval of the beginning of the existence of this culture monuments in the Upper Volga and forest steppe Don region in the early V millennium BC. This is evidenced by the direct stratigraphy of Dobroye 9 settlement, the general stratigraphy of Ksizovo 6 settlement and burial ground, indirect evidence – bedding of the fragments of pottery in the lower pre-natural soil layers of the Upper Don sites: Universitetskaya 3, Vasilyevsky Kordon 7, Ivnitsa. A burial rite similar to the Upper Volga region, radiocarbon dating and data of the technical and technological analysis of ancient ware are also noted.